A traceable privacy‐aware data publishing platform on permissioned blockchain. Issue 5 (12th February 2022) - Li, Fengyin; Sun, Xueqing; Liu, Peiyu; Li, Xiao; Cui, Yang; Wang, Xiaojiao
Abstract: The data publishing platform based on blockchain has advantages of decentralization, anti‐tampering function, and distributed storage. However, privacy leakage, untraceability, and the data tampering cannot be addressed. In order to solve these problems, this article proposes an aggregation signature scheme based on the bilinear mapping, and proposes a traceable privacy‐aware data publishing platform by applying the aggregation signature scheme to the data publishing platform on permissioned blockchain. Performance analysis shows that the traceable privacy‐aware data publishing platform reduces the communication cost, improves the efficiency of signature verification and transmission, provides the anonymity and traceability for the users in the platform. Abstract : In order to solve some problems of the data publishing platform based on permissioned blockchain, this article proposes an aggregation signature scheme based on the bilinear mapping, and proposes a traceable privacy‐aware data publishing platform by applying the aggregation signature scheme to the data publishing platform on permissioned blockchain.